Ethnomathematics Exploration of Simo Dance and Gringsing Batik Dance from Batang Central Java in Mathematics Learning - Fahmy, Ahmad Faridh Ricky; Saputra, Moh. Alwi Andiansyah; Shandy, Kevin Fredika (Jurnal Pendidikan Matematika, 2024)
Culture in Each region's culture has unique characteristics, which are often expressed through dance. As a cultural form, dance serves as a way to express emotions through body movements. In Batang Regency, there are two folk traditions called the Simo Dance and Gringsing Batik Dance. The movements of the two dances consist of forward beksan, beksan, and backward beksan movements. This research used a descriptive qualitative method with an ethnographic approach. Observations, interviews and literature studies were carried out as data collection tools. The results indicate that mathematical concepts are present in the dances, including activities such as counting, patterns of hand and foot movements, and floor formations. These involve geometric concepts like plane shapes, spatial shapes, angles, and reflections. Further research can be developed from other aspects, such as clothing and musical notation which are related to mathematics. Budaya di setiap daerah memiliki karakter tersendiri, termasuk kesenian tari. Tari sebagai bentuk budaya merupakan corak ekspresi perasaan yang dituangkan dalam gerakan tubuh. Di Kabupaten Batang, ada sebuah tradisi kerakyatan yaitu Tari Simo dan Tari Batik Gringsing. Gerakan kedua tari tersebut terdiri dari gerakan maju beksan, beksan, dan mundur beksan. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan etnografi. Adapun observasi, wawancara dan studi pustaka dilakukan sebagai tahap pengumpulan data. Hasil penelitian menunjukkan bahwa terdapat aktivitas matematika seperti menghitung, pola gerakan tangan, kaki, dan pola lantai yang menggunakan konsep geometri seperti bangun datar, bangun ruang, sudut, dan refleksi. Penelitian lebih lanjut dapat dikembangkan kembali dari aspek lain, seperti busana, dan notasi musik serta hubungannya dengan matematika.